Schizophrenia: An Overview - Hamad Farah, Farah (Asian Journal of Pharmaceutics (AJP), 2018)
Schizophrenia is still one of the most mysterious mental disorders that are characterized by delusions, hallucinations, and impaired social behavior. Symptoms of schizophrenia emerge in adolescence and early adulthood while their description is controlled by conventional criteria. The incidence of the mental disorder varies across cultures and migrant groups. Genetic vulnerability overlaps with environmental factors causing individual symptoms and course. This review article focuses on definitions, symptoms, causes, etiology, epidemiology prognosis, history, mechanisms, diagnostics, pathophysiology, possible treatment, and prevention of schizophrenia.